2004
DOI: 10.1182/blood-2004-06-2129
|View full text |Cite
|
Sign up to set email alerts
|

CD157 is an important mediator of neutrophil adhesion and migration

Abstract: CD157, a glycosylphosphatidylinositol (GPI)-anchored protein encoded by a member of the CD38 NADase/ADP-ribosyl cyclase gene family, is expressed on the surface of most human circulating neutrophils. This work demonstrates that CD157 is a receptor that induces reorganization of the cytoskeleton and significant changes in cell shape, and that signals mediated by CD157 act through modulation of cytosolic Ca 2؉ concentration. These signals are independent of the products of CD157's enzymatic activities (ie, cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
89
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 63 publications
(66 reference statements)
4
89
0
Order By: Relevance
“…These conclusions are further supported by the observation that neutrophils from patients with paroxysmal nocturnal hemoglobinuria (which express neither CD157 nor other GPI-anchored molecules as a result of an acquired genetic mutation) (51) are characterized by defective transendothelial migration and adhesion to ECM proteins (11,14).…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…These conclusions are further supported by the observation that neutrophils from patients with paroxysmal nocturnal hemoglobinuria (which express neither CD157 nor other GPI-anchored molecules as a result of an acquired genetic mutation) (51) are characterized by defective transendothelial migration and adhesion to ECM proteins (11,14).…”
Section: Discussionsupporting
confidence: 65%
“…The efficiency of these effects is proportional to the extent of cross-linking, suggesting that the aggregation of many molecules is crucial to the formation of competent signaling microdomains (11). In alignment with this observation, here we demonstrated that anti-CD157 mAb, which can cross-link two molecules, is not sufficient to drag integrins into rafts and, consequently, to transduce activation signals; hence, it blocks transmigration and adhesion, likely preventing leukocyte interaction with a so far unidentified physiological ligand(s).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several glycosylphosphatidylinositol-anchored proteins have been shown to promote cytoskeleton reorganization, changes in cell shape, cell attachment and extracellular matrix-specific migration in neutrophil cells (24), pre-B lymphocytes (25), and breast carcinomas (26). These effects depend on a cross-talk between the glycosylphosphatidylinositolcontaining protein and specific integrins.…”
Section: Invasiveness and Tumor Cell Dissemination Requires Regulatiomentioning
confidence: 99%